Company employees as experimental participants in traffic safety research: Prevalence and implications. (January 2019) - Radun, Igor; Nilsonne, Gustav; Radun, Jenni; Helgesson, Gert; Kecklund, Göran
Highlights: Company employees are sometimes used as research participants in traffic safety research. There are several important ethical and methodological implications. Three types of data were collected. We offer an extensive discussion. Abstract: The use of company employees as experimental participants when testing products, technology or paradigms developed by the same company raises questions about bias in results and research ethics. We aimed to investigate the prevalence of studies authored by car company researchers with car company employees as participants, to assess the risk of bias in such studies, to investigate journal editors' opinions in the field of traffic safety regarding these procedures, and to offer a general discussion about ethical and methodological implications. Three types of data were collected. We (i) examined guidelines and recommendations for authors in eleven selected peer-reviewed journals in the area of traffic safety; (ii) surveyed editors of these journals; and (iii) reviewed articles authored by researchers from a selected group of car manufacturers and published in these journals during 2011–2015. Guidelines and recommendations for authors in the included journals did not mention whether and under what circumstances company employees can be research participants, nor did publishers' general guidelines. However, three out of the four editors who responded to our survey believed that this issue of private company researchers using participants from the same company deserves to be explicitly addressed in their journal's guide for authors. The total number of regular articles and conference papers during 2011–2015 in the eleven journals reviewed was 6763; 95 (1.4%) listed at least one car manufacturer in the authors' affiliations; and out of these, nine included company employees as participants. In summary, company employees are seldom (0.13%) used as research participants in traffic safety research. Nevertheless, the use of company employees as research participants raises questions about bias in results as well as about incursions into the participants' autonomy.